Somatic Variability and the Efficiency of Thermoregulating Mechanisms - Gołąb, Stanisław; Tyka, Aleksander (Anthropological Review, 1992)
Somatic variability and the efficiency of thermoregulating mechanisms was examined on the samples of Thais, Poles and Finns. The intergroup differences indicate the connection with the climatic zones. Thermoregulating efficiency seems to correlate with body built.